The Influence Of Project-Based Learning And Eco-Literacy On Students' Higher-Order Thinking Skills - Okky Ayu Setyowati; Agung Purwanto; Iva Sarifah (Eduvest - Journal of Universal Studies, 2024)
The era of globalization brings new challenges and problems that require innovative solutions. Thus, 21st century education requires students to have higher order thinking skills, one of the learning models for developing these skills is Project Based Learning (PjBL) and ecoliteracy. The purpose of this study was to examine the effect of using Project Based Learning (PjBL) and ecoliteracy learning models separately and together on students' higher order thinking skills. This research is quantitative research with quasi-experiment type. Data collection techniques in this study used ecoliteracy questionnaire instruments and higher order thinking skills tests, as well as observation sheets to observe the implementation of the learning model. As for data analysis, this study used descriptive statistical techniques, tested analytical requirements such as normality and homogeneity tests, and applied inferential statistical analysis with two-way Anava. The results showed that Project Based Learning and ecoliteracy together had a significant positive impact on students' higher order thinking skills. This indicates that the use of Project Based Learning and ecoliteracy is more effective in improving students' higher order thinking skills when compared to using only Project Based Learning or learning models alone.